PERSEPSI PETANI TERHADAP KEBERADAAN KOPERASI “MAJU BERSAMA” DI DESA LONG BELUAH KECAMATAN TANJUNG PALAS BARAT KABUPATEN BULUNGAN KALIMANTAN UTARA - Nopita, Nora; Manumono, Danang; Mawardi, Nanang Kusuma (Fakultas Pertanian UST, 2024)
This research aims to determine farmers' perceptions of the existence of the Maju Bersama cooperative in Long Beluah Village, West Tanjung Palas District, Bulungan Regency, North Kalimantan. The basic method used in this research is a quantitative method. Data collection techniques use questionnaires, observations, and interviews. The sampling method used simple random sampling with a total of 76 respondents. The analytical method in this research uses multiple exponential regression analysis with the determination test (R2), F test, and using the statistical t test (α = 0.05). The results of this research show that age, level of formal education, number of family dependents, land area, length of time as a member, extension support and local government support do not have a significant effect on farmers' perceptions of the existence of cooperatives. Meanwhile, partnership support has a real influence on farmers' perceptions of the existence of cooperatives. This is based on the results of the t test with a significant level, only the partnership support variable shows a significant positive effect on farmers' perceptions. This is proven by a probability value of 0.05 or a value of 0.000 < 0.05. Keywords: Perception, farmers, cooperative, and partnership support